Sensitization of Ventral Tegmental Area Dopamine Neurons to the Stimulating Effects of Ethanol - Ding, Zheng-Ming (2009)
BACKGROUND: Previous studies indicated that chronic alcohol drinking increased the sensitivity of the posterior ventral tegmental area (p-VTA) to the reinforcing effects of ethanol. The current study tested the hypothesis that local exposure of the p-VTA to ethanol would increase the sensitivity of dopamine (DA) neurons to the stimulating effects of ethanol. METHODS: Experiment 1 examined the stimulating effects of ethanol in the p-VTA after a 7-day ethanol pretreatment in the p-VTA. Adult female Wistar rats were pretreated with microinjections of 200 mg% ethanol or artificial cerebrospinal fluid (aCSF) into the p-VTA once a day for 7 days. On the eighth day, rats received a challenge injection of ethanol (100, 200, or 300 mg%) or aCSF into the p-VTA, and extracellular DA levels were measured in the nucleus accumbens (NAc) shell with microdialysis. Experiment 2 examined the stimulating effects of ethanol (200 mg%) after a 3- or 5-day ethanol (200 mg%) pretreatment in the p-VTA. Experiment 3 examined the stimulating effects of ethanol (200 mg%) 7 days after the last of the 7-day ethanol (200 mg%) pretreatments in the p-VTA. RESULTS: Experiment 1: in both aCSF- and ethanol-pretreated rats, the challenge microinjection of ethanol dose-dependently increased DA release in the NAc shell, with significantly greater increases in ethanol-pretreated groups. Experiment 2: the 5-day, but not 3-day, ethanol pretreatment protocol increased the response of p-VTA dopamine neurons to the ethanol challenge. Experiment 3: the increased stimulating effects of ethanol were still evident after 7 days. CONCLUSIONS: The results indicate that repeated local ethanol exposure of the p-VTA produced neuroadaptations in DA neurons projecting to the NAc shell, resulting in a persistent increase in the sensitivity of these neurons to the stimulating effects of ethanol.